Pengaruh Penerapan Sistem Informasi Manajemen terhadap Peningkatan Kinerja Pegawai di Dinas Perhubungan Kota Serang - Munawaroh Munawaroh; Reza Inung Maulana; Achmad Muzaki Adi Saputra; Muhammad Prasetya Utama (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the effect of implementing a Management Information System on employee performance improvement at the Serang City Department of Transportation. Management Information System serves as a tool for data management, reporting, and decision-making support based on information technology. The research uses a quantitative approach with survey methods, by distributing questionnaires to employees from various divisions within the Serang City Department of Transportation. The results show that a structured and integrated Management Information System significantly influences work effectiveness, task completion timeliness, and employee performance accountability. Supporting factors such as system usage training, Information and Communication Technology infrastructure readiness, and leadership commitment further strengthen the positive impact of Management Information System on employee performance. This study recommends strengthening human resources and continuously developing the system to improve transportation services and support bureaucratic reform in the Serang City Department of Transportation.